SUPERVISI TERHADAP KINERJA GURU DAN KUALITAS PENDIDIKAN DI SEKOLAH SMA NEGERI 1 KUALA - Ester Lidia Br. Sembiring; Hamidah Darma; Rabukit Damanik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to conduct an in-depth investigation into the influence between the implementation of educational supervision and teachers’ professional performance, as well as its implications for the enhancement of educational quality at SMA Negeri 1 Kuala. A quantitative approach was employed using a survey design, in which structured questionnaires served as the primary data collection instrument. The sample comprised 38 respondents selected from a total population of 38 teachers. Data were gathered through systematically administered questionnaires to obtain empirical insights into teachers' perceptions of existing supervisory practices. In this context, educational supervision functions as a strategic instrument in fostering teachers’ professional competencies through structured guidance, continuous evaluation, and the provision of constructive feedback. The findings indicate a positive and statistically significant relationship between educational supervision and improved teacher performance, as evidenced by increased instructional effectiveness, greater work discipline, and enhanced pedagogical capabilities. This improvement in teacher performance, in turn, contributes to the overall elevation of educational quality, reflected both in students’ academic achievements and in the general academic climate of the school. Accordingly, a systematic, sustainable, and needs-based supervisory framework constitutes a critical determinant in driving quality transformation at the senior secondary education level.